Low-reactivity casting powder for continuous casting of high-titanium steel slab
By adjusting the protective slag composition, reducing SiO2 activity and interface reactivity, inhibiting crystallization, and reducing slag viscosity through BaF2, the problem of severe slag gold reaction in continuous casting of high-titanium steel slabs is solved, and stable slag performance and good surface quality of casting are achieved.
Patent Information
- Application Number
- CN202510054816.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The prior art has serious slag-gold reactions in the continuous casting of high-titanium steel slabs, which lead to surface quality problems of the casting billets. Especially when steels with high titanium content and wide cross-sections, the reaction is more severe, affecting the continuous casting forward.
By adjusting the BaO, B2O3, Al2O3 and SiO2 content in the protective slag, the activity of SiO2 is reduced, the Gibbs free energy and slag gold reactivity of the interface reaction are reduced, the slag crystallization ability is suppressed, and BaF2 is added to provide F-ion to reduce the slag viscosity, and the precipitation of high-melting point perovskite is inhibited by replacing part of Ca2+.
It realizes the reduction of slag-gold reactivity during continuous casting of high titanium steel, stabilizes slag performance, ensures good lubrication and heat transfer performance during continuous casting, and ensures the stability of the surface quality of the casting billet.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of protective slag, and more specifically to a low-reactivity protective slag for continuous casting of high-titanium steel slabs. Background Art
[0002] In recent years, titanium-containing steels include titanium microalloyed steels, IF steels, titanium-containing stainless steels commonly used in daily life (such as 321 and 409 stainless steels), and 825 alloys. These steels are widely used in aerospace, mining machinery, engineering vehicles, medical equipment and other fields. In the metallurgical field, steels with a titanium content of ≥0.2% are often called high-titanium steels. Titanium is a relatively active metal that easily undergoes redox reactions with oxide components (SiO2, B2O3, Na2O, Li2O, etc.) in protective slag. However, the main chemical reaction involved is [Ti]+(SiO2)→(TiO2)+[Si], which causes the SiO2 content in the CaO-SiO2-based protective slag to decrease, the TiO2 content to increase, and the slag basicity to increase, further leading to drastic changes in the lubrication and heat transfer functions of the protective slag. Especially when casting steel with higher titanium content, the above reaction will be more intense, and the physical and chemical properties of the slag will deteriorate more seriously, which will inevitably cause quality problems such as transverse cracks and longitudinal cracks on the surface of the ingot, and even lead to steel leakage accidents in severe cases.
[0003] The present invention designs a low-reactivity continuous casting protection slag for continuous casting of high-titanium steel slabs (w[C]=0.25-0.3%, w[Ti]=0.4-1.0%), which is intended to reduce the activity of SiO2, reduce the interface reaction Gibbs free energy and slag-metal reactivity, inhibit the slag crystallization ability, ensure the stability of the composition and performance during the continuous casting process, and make it have good control of heat transfer and lubrication performance, thereby ensuring the surface quality of the casting slab by adjusting the contents of BaO, B2O3, Al2O3 and SiO2 in the protection slag.
[0004] Chinese patent CN 110315040B discloses a protective slag for high-carbon and high-titanium wear-resistant steel (w[C]>0.5%, w[Ti]>1.6%), the characteristic of which is that the basicity CaO / SiO2 is controlled in the range of 0.8~1.3, the slag increases MnO and Li2O, adjusts the physical and chemical properties of the protective slag, and effectively eliminates the solid condensate at the steel slag interface when casting steel with a cross-sectional size of 150mm×(1800~3200)mm. However, when casting steel with a high titanium content and a wide cross-sectional size, the slag-metal reaction of this type of protective slag is more intense, affecting the continuous casting process and causing defects such as longitudinal cracks and transverse cracks on the surface of the ingot.
[0005] Chinese patent CN 113953472A discloses a continuous casting protective slag for high titanium steel and its preparation method. The slag corresponds to steel with a titanium content of 0.3-2.0%. The characteristics of the protective slag are that it effectively reduces the reactivity of substances such as Fe2O3, Al2O3, Na2O, B2O3 and Ti in the steel, stabilizes the performance of the protective slag, and introduces 3-10wt% Li2O and 35-50wt% BaO to effectively prevent the formation of high-melting point perovskite. The slag has a certain crystallization ability, which helps to control heat transfer. However, the protective slag will no longer be applicable to slabs.
[0006] Chinese patent CN 118147523 A provides a protective slag for a low-carbon, high-titanium, high-chromium steel thin slab, the Ti content of which is 0.07-0.13%. The protective slag for this steel is characterized by a melting point of 980-1050°C and a viscosity of 0.09-0.10 Pa·s, but is no longer applicable to the steel with a high titanium content (w[Ti]=0.4-0.6wt%) used in the present invention.
[0007] Chinese patent CN113102702B invented a high-basicity, low-reactivity continuous casting protective slag for high-titanium steel. The main feature of this slag is that a certain amount of TiO2 is added to reduce the activity of SiO2, and SrO, BaO and ZnO are added to inhibit the precipitation of high-melting-point perovskite crystals to ensure the glassiness of the slag. At the same time, Chinese patent CN111531140A announced a high-titanium oxide continuous casting protective slag for titanium-containing steel. This slag is aimed at high-titanium steel with a titanium content of 0.1 to 0.8%. The characteristics of the protective slag are that 10 to 20% TiO2 is added to inhibit the reactivity of the steel slag and reduce the changes in the physical and chemical properties of the protective slag. At the same time, BaO, Li2O and B2O3 are added to adjust the glassiness of the slag. And, Chinese patent CN113751681 B relates to a protective slag suitable for continuous casting of high-titanium steel. For steels with a titanium content of 0.4-1.0%, the slag is characterized by not containing fluorine elements, but containing reactive components SiO2, Na2O, Li2O, and TiO2. The protective slags involved in the above three patents all contain TiO2, which is easy to react with carbon in the slag and N2 in the air during the melting process of the protective slag to generate high-melting-point TiC or Ti(C, N) and other substances; at the same time, too much TiO2 is easy for CaO to form high-melting-point calcium titanium minerals, and the protective slag has a strong crystallization ability, which affects the casting lubrication and smoothness, causing problems with the surface quality of the ingot.
[0008] Chinese patent CN114029462 A discloses a continuous casting protective slag containing rare earth oxides for high-titanium and low-aluminum steel. The protective slag is characterized by containing 12-15% Ce2O3, as well as relatively low content of CaO and SiO2, and 1-4% TiO2. This slag is targeted at steels with Ti content of 0.8-1.2% and Al content of 0-0.2%. The casting temperature of the steel corresponding to the rare earth oxide protective slag involved in the patent is as low as 1425-1440℃, which is not suitable for the high-titanium steel of the patent. In addition, the TiO2 contained in the slag will generate high melting point Ti (C, N), which affects the stability of the slag performance and causes surface quality defects of the ingot.
[0009] Chinese patent CN108127094A discloses a non-reactive protective slag for high titanium steel, which is characterized by a CaO-Al2O3-BaO slag system with a low CaO content, which reduces the absorption of titanium oxide inclusions and the formation of perovskite by the protective slag, and does not contain reactive components such as SiO2, Na2O and B2O3. However, 4-10% TiO2 is added to the slag, which will also generate Ti(C, N) during the melting process, affecting the continuous casting process and the stability of the protective slag performance.
[0010] Chinese patent CN114472824A provides a continuous casting crystallizer protection slag for titanium-containing steel, which is characterized by CaO / SiO2 of 1.0-1.1 and contains reactive components Na2O and B2O3. When this type of protection slag is used in high-titanium content steel, the violent slag reaction will cause the precipitation of high-melting point material perovskite, deteriorate the lubrication and heat transfer properties of the protection slag, affect the continuous casting process, and cause surface quality problems of the ingot.
[0011] Chinese patent CN110315039A proposes the application of a fluorine-free protective slag in the continuous casting of titanium-containing steel. The slag is characterized by not containing fluorine elements and containing reactive components SiO2, Na2O, Li2O, and B2O3. The slag is suitable for steels with a titanium content of 0.02 to 0.1 wt%. When the titanium content of the steel is too high, the slag reacts violently, the slag performance deteriorates seriously, and the continuous casting is affected.
[0012] Japanese patent JP2017087273 (A) designs a trouble-free continuous casting protective slag for titanium-containing steel (Ti greater than 0.01%) and solves the problem of precipitation of perovskite crystal phase. It proposes CaO / SiO2≥2.2, SiO20~15wt%, Al2O315~35wt%, flux F less than 20wt%, Na2O+Li2O 10~20wt%, and MgO+MnO2+ZrO2+B2O3 less than 5wt%. However, the steel type targeted by the slag is not suitable for the wear-resistant high-titanium steel of this patent.
[0013] Japanese patent JP2012223807A proposes a method for continuous casting of titanium-containing wear-resistant steel (Ti: 0.1~1.0wt%), which uses slag containing SiO2 in the protective slag for continuous casting. However, this slag will undergo a steel slag reaction, in which the SiO2 content decreases and the TiO2 content increases, increasing the probability of perovskite production. Especially when casting steels with a high titanium content, this reactive slag will no longer be suitable for the casting of high-titanium steel.
[0014] Korean patent EP3127632 (A1) provides a protective slag for preventing longitudinal cracking of slabs for continuous casting of titanium-containing hypoperitectic steel (Ti: 0.1~1.2wt%). The protective slag composition is characterized by containing CaO, SiO2, alkali metal oxides and fluorides. This CaO-SiO2 protective slag still has steel slag reaction, the slag performance deteriorates, affects the smooth continuous casting, and has strict requirements on the continuous casting process parameters. However, its physical and chemical properties will no longer be suitable for the high titanium content steel used in this description. Summary of the invention
[0015] 1. Technical problem to be solved by the invention
[0016] In view of the defects and shortcomings of the prior art, the present invention provides a low-reactivity protective slag for continuous casting of high-titanium steel slabs. The present invention aims to provide a low-reactivity protective slag suitable for continuous casting of high-titanium steel slabs, which aims to reduce the reactivity of slag metal by reducing the SiO2 content and increasing the Al2O3 content in the protective slag; adding BaF2 can not only provide F - ions to reduce slag viscosity and provide Ba 2+ Replacement of part of Ca 2+ To inhibit the precipitation of high melting point perovskite; add an appropriate amount of B2O3 to improve the lubrication and glass properties of the slag. Low-reactivity protective slag reduces the reactivity of slag metal during casting, and the slag performance is more stable during use, with good lubrication and heat transfer control characteristics, so as to achieve high-titanium steel multi-furnace continuous casting and good surface quality of the ingot.
[0017] 2. Technical solution
[0018] In order to achieve the above object, the technical solution provided by the present invention is:
[0019] The invention discloses a low-reactivity protective slag for continuous casting of high-titanium steel slabs, wherein the mass percentages of the protective slag are as follows: CaO: 10%-35%, BaF2: 10%-25%, SiO2: 1%-50%, Al2O3: 5%-35%, Na2O: 2%-15%, Li2O: 4%-10%, MgO≤5%, Fe2O3≤2%, and B2O3: 0-3%.
[0020] Furthermore, the chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.26, CaO: 11.26%, SiO2: 43.26%, Al2O3: 10.88%, Na2O: 12.45%, Li2O: 5.82%, MgO: 1.20%, BaF2: 15.06%, B2O3: 0.04%, Fe2O3: 0.03%.
[0021] Furthermore, the chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.33, CaO: 15.47%, SiO2: 46.72%, Al2O3: 7.45%, Na2O: 10.37%, Li2O: 5.23%, MgO: 1.21%, BaF2: 11.61%, B2O3: 1.32%, Fe2O3: 0.62%.
[0022] Furthermore, the chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.35, CaO: 14.24%, SiO2: 40.20%, Al2O3: 9.28%, Na2O: 12.32%, Li2O: 4.28%, MgO: 4.29%, BaF2: 14.62%, B2O3: 0.02%, Fe2O3: 0.75%.
[0023] Furthermore, the chemical composition and mass percentage of the protective slag are as follows: CaO: 30.48%, SiO2: 3.13%, Al2O3: 32.48%, Na2O: 2.47%, Li2O: 9.11%, MgO: 0.63%, BaF2: 21.62%, B2O3: 0.03%, Fe2O3: 0.05%.
[0024] Furthermore, the metallurgical properties of the low-reactivity continuous casting protection slag are: melting point 850-1100°C, viscosity 0.05-0.45 Pa·s at 1300°C.
[0025] 3. Beneficial effects
[0026] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0027] The characteristics of the present invention are: (1) Compared with traditional CaO-SiO2 slag, the low-reactivity protective slag for continuous casting of high-titanium steel slabs described in the present invention is a low-reactivity slag. The main reaction in the present invention is the reaction between (SiO2) and [Ti] in high-titanium steel. By reducing the SiO2 content in the original slag, the absolute value of the reaction Gibbs free energy is reduced, thereby effectively inhibiting the slag-metal reaction.
[0028] (2) Compared with the traditional protective slag, the addition of the oxide Al2O3 in the protective slag of the present invention can reduce the reactivity of the steel slag, stabilize the viscosity and melting temperature of the protective slag within a suitable range (0.05-0.45 Pa·s), and ensure the smooth casting of high-titanium steel.
[0029] (3) The protective slag of the present invention is a low-reactivity protective slag for continuous casting of high-titanium steel slabs. The main physical and chemical properties of the slag are controlled by CaO, BaF2, Na2O and Li2O. The addition of BaF2 can provide F- to reduce the viscosity of the slag and provide Ba 2+ Replacement of part of Ca 2+ It can inhibit crystallization and control the precipitation of perovskite. A higher content of Li2O can reduce the melting point and viscosity of the slag, and the appropriate addition of B2O3 can ensure the glassiness of the slag, which is intended to ensure the stability of the metallurgical properties of the slag during the continuous casting process and maintain good lubrication and heat transfer properties. It is suitable for high-titanium steel. DETAILED DESCRIPTION
[0030] The present invention is further described below in conjunction with the embodiments: wherein the impurities in each embodiment are MgO≤5% and Fe2O3≤2%:
[0031] Example 1
[0032] The present embodiment provides a low-reactivity protective slag for continuous casting of a high-titanium steel slab, and the mass percentages of the protective slag are as follows: CaO / SiO2=0.26, CaO: 11.26%, SiO2: 43.26%, Al2O3: 10.88%, Na2O: 12.45%, Li2O: 5.82%, MgO: 1.20%, BaF2: 15.06%, B2O3: 0.04%, Fe2O3: 0.03%.
[0033] Preparation and testing methods: The above-mentioned protective slag design components are weighed and prepared with chemically pure reagents in proportion. After mechanical stirring and mixing, the sample is placed in a graphite crucible and then placed in a high-temperature MoSi2 furnace. The temperature is raised to 1300℃ and kept warm for 30 minutes to ensure that the protective slag is melted and mixed evenly. The viscosity and melting temperature of the continuous casting crystallizer protective slag are measured using relevant equipment, and the measurement standards adopt the metallurgical industry standards YB / T 185-2017 and YB / T 186-2014.
[0034] The main chemical components, mass percentage (%) and metallurgical performance indicators of the protective slag are shown in Table 1.
[0035] Example 2
[0036] The present embodiment provides a low-reactivity protective slag for continuous casting of a high-titanium steel slab, and the mass percentages of the protective slag are as follows: CaO / SiO2=0.33, CaO: 15.47%, SiO2: 46.72%, Al2O3: 7.45%, Na2O: 10.37%, Li2O: 5.23%, MgO: 1.21%, BaF2: 11.61%, B2O3: 1.32%, Fe2O3: 0.62%.
[0037] Preparation and testing methods: Same as Example 1.
[0038] The main chemical composition (wt%) and metallurgical performance indicators of the protective slag are shown in Table 1.
[0039] Example 3
[0040] The present embodiment provides a high-titanium steel continuous casting low-reactivity protective slag, and the mass percentages of the protective slag are as follows: CaO / SiO2=0.35, CaO: 14.24%, SiO2: 40.20%, Al2O3: 9.28%, Na2O: 12.32%, Li2O: 4.28%, MgO: 4.29%, BaF2: 14.62%, B2O3: 0.02%, Fe2O3: 0.75%.
[0041] Preparation and testing methods: Same as Example 1.
[0042] Example 4
[0043] The present embodiment provides a high-titanium steel continuous casting low-reactivity protective slag, and the mass percentages of the protective slag are as follows: CaO: 30.48%, SiO2: 3.13%, Al2O3: 32.48%, Na2O: 2.47%, Li2O: 9.11%, MgO: 0.63%, BaF2: 21.62%, B2O3: 0.03%, and Fe2O3: 0.05%.
[0044] Preparation and testing methods: Same as Example 1.
[0045] The main chemical composition (wt%) and metallurgical performance indicators of the protective slag are shown in Table 1.
[0046] Comparative Example 1
[0047] A mold slag in this comparative example is composed of the following mass percentages: CaO / SiO2=1.02, CaO: 33%, SiO2: 32.5%, Al2O3: 3.72%, MgO: 2.28%, Na2O: 9%, Li2O: 1.85%, F - : 7%, MnO: 2.8%, C: 4%, and the remaining components are impurities.
[0048] Preparation and testing methods: Same as Example 1.
[0049] Comparative Example 2
[0050] A protective slag in this comparative example consists of the following mass percentage ratios: CaO / SiO2=1.2, CaO: 36.46%, SiO2: 30.39%, Al2O3: 5%, MgO: 2%, Na2O: 9%, Li2O: 0.5%, MnO: 2%, B2O3: 7.65%, Fe2O3: 4%.
[0051] Preparation and testing methods: Same as Example 1.
[0052] Comparative Example 3
[0053] A protective slag in this comparative example consists of the following mass percentages: CaO: 30%, SiO2: 14%, Al2O3: 19%, MgO: 3%, Na2O+B2O3+Li2O: 10%, C: 3%, and TiO2: 12%.
[0054] Preparation and testing methods: Same as Example 1.
[0055] The main chemical composition (wt%) and metallurgical performance indicators of the protective slag are shown in Tables 1 and 2.
[0056] Examples 1-4 are low-reactivity protective slag for continuous casting of high-titanium steel. The results of laboratory slag-metal reaction experiments and on-site continuous casting production practices show that low-reactivity protective slag for continuous casting of high-titanium steel can meet the casting requirements. The protective slag has suitable lubrication and stable heat transfer properties during the continuous casting process, and the surface quality of the ingot is significantly improved.
[0057] Table 1 Chemical composition of mold slag in Examples 1-4 and performance indicators of slag before and after reaction
[0058]
[0059] Table 2 Performance index test results of protective slag in comparative examples 1 to 3
[0060]
[0061]
[0062] It can be seen from the above indicators that the low-reactivity protective slag for continuous casting of high-titanium steel slabs prepared in Examples 1-4 has better performance indicators and parameters, such as melting point, viscosity and applicability, than comparative examples 1-3; the performance of the low-reactivity protective slag for continuous casting of high-titanium steel slabs prepared in Examples 1-4 meets the requirements of process parameters in the actual continuous casting production process, especially when slag-metal reaction occurs during the continuous casting process, it still maintains suitable lubrication and heat transfer properties.
[0063] The slag of Example 2 was used to carry out on-site casting experiments. The analysis results of slag samples showed that, compared with the traditional CaO-SiO2 slag casting of high-titanium steel, the precipitation of perovskite (CaTiO3) was reduced, the friction curve was stable, the temperature field in the crystallizer was stable, and it had good control of heat transfer and lubrication effects. Two furnaces were cast smoothly on-site, there were no slag bars and obvious liquid level fluctuations in the crystallizer, the liquid level in the crystallizer was active, and the problems of longitudinal and transverse cracks on the surface of the ingot were significantly improved.
[0064] The slag of Example 4 was used to carry out on-site casting experiments. The analysis results of slag samples showed that compared with the traditional CaO-SiO2 slag casting of high-titanium steel, two furnaces of continuous casting were successfully achieved on-site, there were no slag bars and obvious liquid level fluctuations in the crystallizer, the liquid level in the crystallizer was active, and the problems of longitudinal and transverse cracks on the surface of the ingot were significantly improved.
[0065] In view of the above-mentioned deficiencies in the prior art, the present invention aims to provide a mold protection slag suitable for continuous casting of high-titanium steel slabs. During the continuous casting process, the protection slag (SiO2) reacts with [Ti] in the molten steel, and the slag performance remains stable during the slag-metal reaction during the casting process, that is, the protection slag has good lubrication and heat transfer control characteristics throughout the continuous casting process, thereby ensuring smooth continuous casting of high-titanium steel and good surface quality of the ingot.
[0066] Specifically, the continuous casting mold protection slag of the present invention reduces the reactive component (SiO2) in the traditional slag, reduces the (SiO2) content in the slag to inhibit the slag metal reactivity by adding a relatively high content of Al2O3 (5-30%), and 2+ Replacement of part of Ca 2+ In order to inhibit the precipitation of perovskite, a small amount of B2O3 is added to ensure the glassiness of the slag. During the continuous casting process, the slag metal reaction will maintain the physical and chemical properties of the protective slag within a stable casting range to ensure smooth continuous casting. Among them, the basic metallurgical properties of the low-reactivity protective slag for continuous casting of high-titanium steel slabs are as follows: melting point 850-1100℃, viscosity 1300℃ 0.05-0.45Pa·s, suitable for continuous casting production of high-titanium steel slabs with w[Ti] = 0.4% to 1.0%.
[0067] In the mold slag of the present invention, CaO and SiO2 are the main components of the mold slag, which have wide sources and low prices. The reduction of the CaO / SiO2 ratio can increase the viscosity and improve the lubricity of the mold slag. CaO can enhance the ability of steel to absorb oxide inclusions, while O 2- The release of ions can reduce the viscosity of the slag. In the present invention, the lower CaO content can weaken the precipitation of perovskite; SiO2 is a network former that can increase the polymerization degree of the slag. CaO is controlled in the range of 10% to 35%, and SiO2 is controlled in the range of 1% to 50%.
[0068] BaF2 is a flux that can provide F - To reduce the slag viscosity, while providing Ba 2+ Ion replacement of part of Ca 2 + In order to inhibit slag crystallization, control the precipitation of perovskite, improve the lubrication and crystallization characteristics of the slag, and ensure the stability of the liquid slag during use, the present invention controls the BaF2 content within the range of 10% to 25%.
[0069] Al2O3 can reduce the reactivity of slag in low-reactivity continuous casting protection slag for continuous casting of high-titanium steel slabs. Adding a proper amount of Al2O3 can improve the lubrication and control heat transfer performance of the slag. Therefore, the present invention controls the Al2O3 content to 5% to 35%.
[0070] Li2O is often used as one of the most effective fluxing agents in continuous casting mold slag. It can reduce the melting point of slag (1wt% Li2O reduces the melting point by 30-48°C) and viscosity, and inhibit crystallization within a relatively low content range. When the content is too high, the effect on the physicochemical properties of the slag is not significant, and Li2O is expensive. Therefore, the present invention controls the content of Li2O to be within the range of 4% to 10%.
[0071] MgO is added to the slag as a basic oxide. When its content is less than 6%, the viscosity, melting point and transition temperature can be effectively reduced. When the content is too high, the slag properties show the opposite law. Therefore, the present invention controls MgO≤5%.
[0072] Fe2O3 is an inevitable impurity introduced into the mold slag, and the present invention controls Fe2O3 to be ≤2%.
[0073] B2O3 is an acidic oxide that can effectively improve the glass properties of protective slag. Adding an appropriate amount of B2O3 can reduce the melting point and viscosity, and improve the lubricity and glass properties of liquid slag. When the content is low, the influence of slag-gold reaction can be ignored. The present invention controls the B2O3 content within the range of 0 to 3%.
[0074] The above is a schematic description of the present invention and its implementation methods, which is not restrictive. Therefore, if a person skilled in the art is inspired by it and designs a structure and implementation method similar to the technical solution without creative design without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A low-reactivity mold slag for continuous casting of high-titanium steel slabs, characterized in that: The mass percentages of the protective slag are as follows: CaO: 10%-35%, BaF2: 10%-25%, SiO2: 1%-50%, Al2O3: 5%-35%, Na2O: 2%-15%, Li2O: 4%-10%, MgO≤5%, Fe2O3≤2%, and B2O3: 0-3%.
2. The low-reactivity mold slag for continuous casting of high-titanium steel slab according to claim 1, characterized in that: The chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.26, CaO: 11.26%, SiO2: 43.26%, Al2O3: 10.88%, Na2O: 12.45%, Li2O: 5.82%, MgO: 1.20%, BaF2: 15.06%, B2O3: 0.04%, Fe2O3: 0.03%.
3. The low-reactivity mold slag for continuous casting of high-titanium steel slab according to claim 1, characterized in that: The chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.33, CaO: 15.47%, SiO2: 46.72%, Al2O3: 7.45%, Na2O: 10.37%, Li2O: 5.23%, MgO: 1.21%, BaF2: 11.61%, B2O3: 1.32%, Fe2O3: 0.62%.
4. The low-reactivity mold slag for continuous casting of high-titanium steel slab according to claim 1, characterized in that: The chemical composition and mass percentage of the protective slag are as follows: CaO / SiO2=0.35, CaO: 14.24%, SiO2: 40.20%, Al2O3: 9.28%, Na2O: 12.32%, Li2O: 4.28%, MgO: 4.29%, BaF2: 14.62%, B2O3: 0.02%, Fe2O3: 0.75%.
5. The low-reactivity mold slag for continuous casting of high-titanium steel slab according to claim 1, characterized in that: The chemical composition and mass percentage of the protective slag are as follows: CaO: 30.48%, SiO2: 3.13%, Al2O3: 32.48%, Na2O: 2.47%, Li2O: 9.11%, MgO: 0.63%, BaF2: 21.62%, B2O3: 0.03%, Fe2O3: 0.05%.
6. The low-reactivity mold slag for continuous casting of high-titanium steel slab according to claim 1, characterized in that: The metallurgical properties of the low-reactivity continuous casting protection slag are as follows: a melting point of 850-1100° C. and a viscosity of 0.05-0.45 Pa·s at 1300° C.
Citation Information
Patent Citations
Non-reactive casting powder for high titanium steel
CN108127094A
Application of fluoride-free casting powder during titanium-containing steel continuous casting
CN110315039A
A protective slag for continuous casting crystallizers of high-carbon, high-titanium wear-resistant steel
CN110315040B
A high-basicity, low-reactivity continuous casting protective slag for high-titanium steel and its preparation method.
CN113102702B
A continuous casting protective slag suitable for high-titanium steel
CN113751681B